Implementasi Program CSR PT. PAL Indonesia Melalui Kegiatan Donor Darah - Lena Saidatul Muawanah; Rini, Hesty Prima (Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
PT PAL Indonesia's Corporate Social Responsibility (CSR) program in the form of blood donation and health checks is a tangible manifestation of the company's concern for humanitarian and public health issues. This program is carried out in a structured manner through a persuasive-educational approach and in collaboration with the Indonesian Red Cross (PMI). The results of the implementation show an increase in social solidarity, voluntary participation of employees, and a significant contribution to the availability of national blood stocks. In addition to having a positive impact externally, this program also provides health benefits and internal motivation for employees. This program is an example of sustainable CSR that can be replicated by other companies.Program Corporate Social Responsibility (CSR) PT PAL Indonesia dalam bentuk kegiatan donor darah dan cek kesehatan merupakan wujud nyata kepedulian perusahaan terhadap isu kemanusiaan dan kesehatan masyarakat. Program ini dilaksanakan secara terstruktur melalui pendekatan persuasif-edukatif serta bekerja sama dengan Palang Merah Indonesia (PMI). Hasil implementasi menunjukkan peningkatan solidaritas sosial, partisipasi sukarela karyawan, serta kontribusi signifikan terhadap ketersediaan stok darah nasional. Selain berdampak positif secara eksternal, program ini juga memberi manfaat kesehatan dan motivasi internal bagi karyawan. Program ini menjadi contoh CSR berkelanjutan yang dapat direplikasi oleh perusahaan lain.